The Nasab of A Corpse to Its Mother in the Practice of Talkin in Keudah-Malaysia and Aceh-Indonesia: Nasab Mayat Kepada Ibunya Dalam Praktik Talkin Di Keudah-Malaysia Dan Aceh-Indonesia - Yahya, Faisal; Bin Faiz, Muhammad Faiyadh; Wahyuni, Sri (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2024)
Talking to the corpse is a tradition that has been practiced for a long time in Islamic society in the archipelago, the form of implementation is very diverse. The naming of the corpse in the practice of talking to the mother is different from the lineagein fiqh which is generally referred to the father. The use of pronunciation is also different, the Kedah Malaysian community carries out talking using Malay, while the Acehnese community in Indonesia uses Arabic. This study answers the background of the differences in the use of the talkin phrase in Kedah-Malaysia and Aceh-Indonesia and the reference basis used. Answering this objective, interviews were conducted with several religious figures and observations were made on the talkin activities and relevant documents were reviewed. After obtaining qualitative data, the data were then compared using comparative analysis. The results of the study found that the process of implementing talking between Kedah-Malaysia and Aceh-Indonesia was almost the same, but in the use of the talkin phrase by the Kedah-Malaysian community using Malay which was adopted from the hadith narrated by al-Ṭabrānī in a visible way as their reference. Meanwhile, in Aceh-Indonesia, they practice the reading of talkin the corpse in the History of al-Ṭabrānī, but in narrating the corpse using the concept of lineage in fiqh because the aim is to make it easier. Ulama Keudah Malaysia and Aceh admit that narrating the corpse to the mother in the practice of talkin is more important than to the father.